(untitled) (Journal of Atomic and Molecular Sciences, 2013)
Based on the Gupta-type semi-empirical inter-atomic many-body potential, the melting behaviors of the Al_196 cluster are systematically studied by using the molecular dynamics method combined with the annealing and quenching techniques. Our simulation results show that from different initial structures one can observe quite different melting behaviors. From a relatively low-energy stable geometry, two peaks occur clearly in the heat capacity curve; But only one peak dominates the heat capacity curve if starting from the ground-state or its closer low energy structures. Reasons of the different melting properties of the Al196 cluster are explored by analyzing the energy distributions of the simulated quenching structures of Al_196 at different temperatures.